THE IMPACT OF SOCIAL MEDIA: SHAPING SOCIETY AND INDIVIDUALS - Musayeva Mehriniso , (TADQIQOTLAR.UZ, 2023)
Social media has undoubtedly transformed our society, connecting people, shaping public discourse, and influencing individual behavior. It has provided unprecedented opportunities for communication, information sharing, and business growth. However, it also carries risks, such as the spread of misinformation, negative impacts on mental health, and privacy concerns. As social media continues to evolve, it is essential to strike a balance between leveraging its benefits and addressing its challenges to create a healthier and more responsible digital environment.